Who dares, wins? A sibling analysis of tertiary education transition in Germany - Tamás Keller; Guido Neidhöfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Past studies have found that parental background has a considerable impact on educational decisions. Our knowledge is, however, still limited regarding educational transitions later in life, such as into tertiary education. Is parental background a predominant factor in this relatively late educational decision, or do individual talent and determination have an impact of their own? We address this question by decomposing the probability of success - regarded by rational choice models in sociology as a major component in the explanation of educational choices - as a function of observable and unobservable characteristics, using school grades and subjective perceptions about future educational success. Tocontrol for the overall effect of family background, a sibling analysis is performed. The data is derived from the German Socioeconomic Panel (SOEP), where we can follow those pupils who participated in the survey at the age of 17 later in life. Our results are twofold. Parental background (through school grades) exerts a strong influence at the time of transition to university; however, subjective perceptions also have an effect that is independent of parental background.
Keywords: I23; I24; J62; 330; tertiary education transition; sibling analysis; subjective perceptions; rational choice